Restrictions on migration create gender inequality: The story of China's left-behind children - Xuwen Gao; Wenquan Liang; Ahmed Mushfiq Mobarak; Ran Song (Yale University, Economic Growth Center, 2022)
About 11% of the Chinese population are rural-urban migrants, and the vast majority of them (124 million people) possess a rural hukou which severely restrict their children's access to urban public schools. As a result, 61 million children are left behind in rural areas. We use a regression-discontinuity design based on school enrollment age cutoffs to document that migrants are significantly more likely to leave middle-school-aged daughters behind in poor rural areas without either parent present when schooling becomes expensive, compared to middle-school-aged sons. The effect is larger when the daughter has a male sibling. Migrant parents send significantly less remittances back to daughters than sons. Migrants from rural areas adjacent to cities with more restrictive hukou policies are more likely to separate from children as new job opportunities arise in nearby cities due to trade-induced shocks to labor demand. This produces a shift-share IV strategy, when paired with a longitudinal dataset shows that those children complete 3 fewer years of schooling, are 41% more likely to fail high school entrance exams, have worse mental and physical health, and remain poor as adults. Although China's hukou mobility restrictions are not gender-specific in intent, they have larger adverse effects on girls.
Keywords: J13; J16; R23; 330; Migration; hukou; Left-Behind Children; Gender Inequality